Phenotypic and Genotypic Variation in Czech Forage, Ornamental and Wild Populations of Reed Canarygrass. Issue 5 (1st September 2016) - Anderson, Neil O.; Kávová, Tereza; Bastlová, Daša; Čurn, Vladislav; Kubátová, Barbora; Edwards, Keith R.; Januš, Vojtěch; Květ, Jan
Abstract : Reed canarygrass ( Phalaris arundinacea L.) is native to Europe and North America, being invasive in the latter since the 20th century. No phenotypic differences have been found in plants from each continent; genetic analyses have been controversial—implicating or exonerating forage/ornamental cultivars for spread throughout North America. Within central Europe, particularly the Czech Republic, it is unknown whether wild genotypes and cultivars are genetically and phenotypically similar. The objectives of this study were to compare commercial forage and ornamental cultivars sold within the Czech Republic with wild genotypes from native populations along major Czech rivers and characterize the extent of phenotypic and genetic variation. Several phenotypic traits differentiated among genotypes and populations (initial tiller fresh weight, stem dry weight [DW], whole plant above‐ and belowground DW, total no. of tillers, percent cover, crown area, height, leaf and node number). Genetic markers (inter‐simple sequence repeats [ISSRs]) clearly differentiated ornamental cultivars from wild P. arundinacea . 'Chrastava', the Czech forage and biomass cultivar was genetically similar to wild genotypes, which have most of the genetic diversity within, rather than among, populations. Cluster analyses showed ornamental cultivar ramets to be heterogeneous, most likely due to clonal mix up or mutations.